Analysis of Coffee Pulper Machine Performance: A Comprehensive Review of Methods, Technologies, and Influencing Factors - Allo, Bartolomeus Rante (International Journal of Contemporary Sciences (IJCS), 2024)
This study aims to analyse the performance of a coffee peeling machine through a comprehensive review of the methods, technologies, and influencing factors that affect the effectiveness of the machine. A literature review was conducted to gather current and pertinent information on the latest developments in peeling methods, technology applications, and influencing factors affecting machine performance. Analyses of diverse operational methods, ranging from conventional methods to recent innovations, provided in-depth insights into the variety of coffee hulling techniques. Influencing factors such as coffee bean moisture, bean size, and machine operating conditions were analysed to understand the complexity of interactions between variables. The conclusions of this study contribute to the practical and theoretical understanding of the factors affecting the performance of coffee hulling machines, providing a foundation for further development in this field